Modular conceptual modelling approach and software for river hydraulic simulations. (September 2015) - Wolfs, Vincent; Meert, Pieter; Willems, Patrick
Abstract: Numerous applications in river management require computationally efficient models that can accurately simulate the state of a river. This paper presents a reduced complexity modelling approach that emulates the results of detailed full hydrodynamic models. Its modular design based on virtual reservoirs allows users to combine different model structures depending on the river dynamics and intended use. A semi-automatic software tool (Conceptual Model Developer, CMD) was developed to facilitate model set-up. To prevent instabilities during simulations, a highly efficient discrete calculation scheme is presented with a variable time step. To illustrate the effectiveness of the presented approach, the Marke River in Belgium was conceptualized based on simulation results of a detailed model. Results show that the derived conceptual model mimics the detailed model closely, while the calculation time is reduced by more than 2000 times. Finally, several applications are discussed that employ conceptual models built according to the presented approach. Highlights: A reduced complexity modelling approach for river hydraulic simulations is proposed. Flexible modular framework that incorporates a variety of structures and techniques. A software tool (CMD) was created to speed-up and facilitate model set-up. A discrete calculation scheme was developed with time and space varying time step. A case study and discussion of applications illustrate the approach's effectiveness.